ICT maturity as a driver to global competitiveness: a national level analysis - Yunis, Manal M. (2012)
Purpose The purpose of this paper is to examine the role that information and communication technologies (ICT) maturity plays in the achievement of global competitiveness at the country level. The paper investigates the socio‐economic and technological factors that are most likely to be associated with ICT maturity, and then assesses their role in driving the global competitiveness wheel forward. Design/methodology/approach Secondary data were used, based on data sets generated by the World Bank, World Economic Forum, and UNESCO for the years 2003‐2007. The countries common to all reports were included, yielding a study sample of 93 cases. Cluster analysis was used to categorize countries in terms of ICT usage, readiness, and environment. Structural equation modeling was used to test the fit of a model employing these factors. Findings First, it was found that ICT plays an important role in driving a country's global competitiveness forward, with a stronger relationship existing in high readiness countries than in low readiness countries. Second, ICT maturity was found to mediate the relationship between ICT quality and R&D spending on one hand and global competitiveness on the other. Finally, the relationship between R&D spending and global competitiveness was found to be stronger for low readiness countries than for high readiness countries. Practical implications The paper's findings provide insights to managers and government policy makers regarding the effects of economic, social and technological factors on ICT maturity, as well as the relationship between ICT maturity and global competitiveness. Such insights can influence the standards, programs, and strategies that governments implement in order to attain and maintain global competitiveness. Originality/value The paper presents a holistic model that depicts the ICT maturity factors and their dynamic contributions to global competitiveness. Despite the considerable contributions of existing research in this domain, there is a lack of substantive research that examines the relationship at the country level between ICT maturity and its indicators on one hand and global competitiveness on the other. The paper is an attempt to fill this gap.